MEANING OF ARABIC VOCABULARY (DESCRIPTION OF CHANGES IN ARABIC LANGUAGE MUFRODAT MEANING) - Tuti Hardianti Hasibuan; Ary Myftakhul Huda; Neldi Harianto (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2021)
Arabic is a product of a civilization that is a guide for the Muslim community and a reference for understanding the Qur'an, both from the Arabs themselves as native speakers, as well as non-native Arabic. The importance of language covers almost all areas of life because it is everything that is lived, experienced, felt, and thought of to someone that can only be known by others if it has been expressed in language, either written or spoken language. One of the features of Arabic according to other languages ??is that Arabic is very rich in using vocabulary, both in terms of the number of vocabulary and in terms of its form. This study used qualitative research methods. This research is qualitative. The method used is a descriptive method with data collection techniques through literature study. The data was collected using reading and writing techniques, then the data was analyzed and presented in the form of a description. this study is a literature review using content analysis techniques (content analysis). Content Analysis is a research technique that is used to make inferences that are replicable and valid in terms of data by taking into account the context. Then the data is analyzed descriptively and analyzed qualitatively to reveal the meaning of word changes and the factors of change. From this research, several examples of changes in meaning are broadened, narrowed, and changed in total meaning